2016
DOI: 10.1186/s40064-016-3070-z
|View full text |Cite
|
Sign up to set email alerts
|

Modified homotopy perturbation method for solving hypersingular integral equations of the first kind

Abstract: Modified homotopy perturbation method (HPM) was used to solve the hypersingular integral equations (HSIEs) of the first kind on the interval [−1,1] with the assumption that the kernel of the hypersingular integral is constant on the diagonal of the domain. Existence of inverse of hypersingular integral operator leads to the convergence of HPM in certain cases. Modified HPM and its norm convergence are obtained in Hilbert space. Comparisons between modified HPM, standard HPM, Bernstein polynomials approach Mand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 24 publications
(45 reference statements)
0
11
0
Order By: Relevance
“…In Eshkuvatov et al. [13] it is shown that both HPM and MHPM give identical solution. In Table 1 comparisons of three methods are given.…”
Section: The Norm Of L −1 ∂Nmentioning
confidence: 98%
See 2 more Smart Citations
“…In Eshkuvatov et al. [13] it is shown that both HPM and MHPM give identical solution. In Table 1 comparisons of three methods are given.…”
Section: The Norm Of L −1 ∂Nmentioning
confidence: 98%
“…are homo-topic as the effectiveness of MHPM, the author has shown many examples. In 2016, Eshkuvatov et al [13] were able successfully implemented the modifed HPM together with Chebyshev polynomials for the following HSIEs of the first kind.…”
Section: The Norm Of L −1 ∂Nmentioning
confidence: 99%
See 1 more Smart Citation
“…What makes a certain hypersingular integral equation efficient is the extent to which that it could be a significant tool for solving a large class of mixed boundary value problems showing up in mathematical physics; especially, the crack problems of fracture mechanics, or water wave scattering problems concerning obstructions; diffracting electromagnetic waves and also aerodynamics problems might be decreased to hypersingular integral equations rather single or disjoint multiple intervals. Ideally, there is an imperative example of hypersingular integral equations of the first kind which has been exercised in dealing with most problems arising in vibration and active control [10][11][12][13][14][15][16][17] 1 p Z 1 À1 uðxÞ ðx À yÞ 2 dx ¼ fðyÞ; ðÀ1 < y < 1Þ (1) Here, f(y) and u(x) are presented as a known function and an unknown function on the finite interval ðÀ1; 1Þ considering the end points conditions uðAE1Þ ¼ 0. In equation 1 ; ðÀ1 < y < 1Þ…”
Section: Introductionmentioning
confidence: 99%
“…Mahmoudi 37 actually formed a new modified Adomian decomposition method to solve a class of hypersingular integral equations of the second kind. Also, Eshkuvatov et al 13 have presented a work regarding to the modified homotopy perturbation method for solving hypersingular integral equations of the first kind. In the present paper, we consider the method mentioned in literature 33,37 and then determine a new modified homotopy perturbation method to actually solve hypersingular integral equation of the first kind.…”
Section: Introductionmentioning
confidence: 99%